Neuraxial anaesthesia in paediatrics. Issue 6 (June 2019) - Marcelino, Ryan; Sawardekar, Amod; Suresh, Santhanam
Abstract: Neuraxial anaesthesia is a valuable aid in the practice of paediatric anaesthesia. Spinal and epidural blockade are used as either the sole anaesthetic or as an adjunct to general anaesthesia, and often confer significant postoperative analgesia. Caudal epidural anaesthesia is used extensively for lower abdominal, urological and orthopaedic procedures in the setting of outpatient surgery. Lumbar and thoracic epidural infusions via a catheter can provide analgesia for chest and upper abdominal procedures. Major complications related to neuraxial catheter placement are uncommon in paediatric anaesthesia, even though block placement is typically after the patient is anesthetized. The use of the ultrasound for real-time visualization during paediatric neuraxial blocks provides an opportunity for observing final catheter position or confirming successful injection into the epidural space.